2008
DOI: 10.1590/s1413-70542008000300043
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas lenhosas de pessegueiro e clones de umezeiros submetidos à aplicação de AIB

Abstract: A utilização do umezeiro ou damasqueiro-japonês (Prunus mume Sieb & Zucc.) como porta-enxerto de Prunus sp. vem despertando grande interesse em função de sua rusticidade, resistência a pragas e doenças, adaptação e, principalmente, por reduzir o porte de pessegueiros e nectarineiras. Visto que trabalhos prévios constataram baixo enraizamento de alguns clones de umezeiro e um estímulo a este processo em estacas herbáceas com uso de 2000 mg.L-1 de AIB, objetivou-se no presente trabalho estudar o enraizamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 4 publications
(1 reference statement)
2
6
0
14
Order By: Relevance
“…Similarly to results presented herein, CHAGAS et al (2008) observed that 2.000mg dm -3 of IBA promoted the highest rooting and calli percentages and the greatest average number of roots on peach and Japanese apricot cuttings. In BORTOLINI et al (2008), IBA was efficient for rooting induction of Tibouchina sellowiana cuttings, independently if used liquid or in powder, being concentrations among 1.500 and 3.000mg dm -3 the best ones; and GARCÍA et al (2005) obtained rooting percentages higher than 80% on cuttings of Gmelina arborea, a species with great domestication potential; and toxicity with higher IBA doses was also observed on cutting propagation of Acca sellowiana, a South American native species, by FRANZON et al (2004).…”
Section: Espécies Desupporting
confidence: 87%
“…Similarly to results presented herein, CHAGAS et al (2008) observed that 2.000mg dm -3 of IBA promoted the highest rooting and calli percentages and the greatest average number of roots on peach and Japanese apricot cuttings. In BORTOLINI et al (2008), IBA was efficient for rooting induction of Tibouchina sellowiana cuttings, independently if used liquid or in powder, being concentrations among 1.500 and 3.000mg dm -3 the best ones; and GARCÍA et al (2005) obtained rooting percentages higher than 80% on cuttings of Gmelina arborea, a species with great domestication potential; and toxicity with higher IBA doses was also observed on cutting propagation of Acca sellowiana, a South American native species, by FRANZON et al (2004).…”
Section: Espécies Desupporting
confidence: 87%
“…IBA promoted higher rooting than 2,4-D for all rootstocks (Table 1). Probably, these results can be explained by the fact that IBA is considered less toxic at high concentrations and has photostability and microbiological stability (OLIVEIRA et al, 2010;OHLAND et al, 2009;CHAGAS et al, 2008). Moreover, the herbicidal effect of 2,4-D, even when applied only to the base of the cuttings, could harm the vital functions of the cuttings, because auxins can induce prejudicial metabolic and biochemical changes, such as in nucleic acids, the plasticity of the cell wall, and the action of the RNA-polymerase enzyme, and, consequently, in the synthesis of nucleic acids and proteins, and can also induce high cell proliferation in tissues, causing stem epinasty and phloem interruption (OLIVEIRA JÚNIOR et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Outros trabalhos na literatura já relatam a utilização da areia como substrato para o enraizamento de estacas de figueira (Ohland et al, 2009), umezeiro (Chagas et al, 2008) e marmeleiro (Pio et al, 2007).…”
Section: Resultsunclassified